The impact of virtual reality on student engagement and learning outcomes in technological learning environment – A SWOT analysis - Nor Hannani Izzati, Abdullah; Eh Phon, Danakorn Nincarean; Nor Saradatul Akmar, Zulkifli; Nur Afiqah, Sahadun; Nur Ariffin, Mohd Zin; Azizah, Mohamad; Andek Nurul Haziqah, Andek Jelantek (Indonesian Society for Knowledge and Human Development, 2025)
Virtual reality (VR) is a transformative educational tool that addresses challenges in student engagement, inclusivity, and learning outcomes. By creating immersive and interactive learning environments, VR enhances motivation, critical thinking, and skill acquisition, particularly in STEM (Science, Technology, Engineering, and Mathematics), healthcare, and engineering disciplines. Its strengths include personalized and gamified experiences that enhance accessibility for students with diverse needs, including those from marginalized and disabled backgrounds. However, VR adoption faces significant barriers, such as technical issues, motion sickness, hardware malfunctions, high costs, and reliance on robust infrastructure, particularly in under-resourced environments. Educator reluctance, driven by a steep learning curve and pedagogical uncertainty, further hinders integration. This study aims to examine the strengths, weaknesses, opportunities, and threats (SWOT) associated with virtual reality (VR) in education, providing a detailed overview. SWOT, a descriptive framework developed in the 1960s for business planning, facilitates a precise analysis by classifying internal strengths and weaknesses alongside external opportunities and threats, making it the preferred tool for this study. Its practical use extends to fields such as engineering, medicine, biology, physics, chemistry, sports, music, and the arts, enabling insights into educational technologies. Despite challenges, VR offers opportunities such as scalability, interdisciplinary applications, and remote learning. Advances in affordable VR systems and hybrid virtual-augmented technologies hold promise for enhancing engagement and learning outcomes across diverse educational environments. A SWOT analysis highlights the potential of VR to address financial constraints and institutional opposition, while also improving inclusivity. Future studies should prioritize long-term evaluations and cost-efficient solutions, ensuring scalable and equitable adoption in education.